2016
DOI: 10.1186/s13578-016-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis reveals the expression of unique transcriptomic signatures in Zika virus infected human neural stem cells

Abstract: BackgroundThe single-stranded RNA Flavivirus, Zika virus (ZIKV), has recently re-emerged and spread rapidly across the western hemisphere’s equatorial countries, primarily through Aedes mosquito transmission. While symptoms in adult infections appear to be self-limiting and mild, severe birth defects, such as microcephaly, have been linked to infection during early pregnancy. Recently, Tang et al. (Cell Stem Cell 2016, doi: 10.1016/j.stem.2016.02.016) demonstrated that ZIKV efficiently infects induced pluripot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
3
37
0
2
Order By: Relevance
“…63 A study carried out using a bioinformatic approach showed that infection of human NPCs results in substantial changes in gene up-and down-regulation. 64 In this context, prominent features are represented by the hyper-expression of genes involved in the regulation of nucleic acid metabolism (hallmark of virus replication) and the down-regulation of genes involved in chromosome segregation and DNA replication and repair. 64 In addition, ZIKV infection of the above-mentioned cells results in the activation of several innate immunity pathways, that are different from those observed in other infections known to cause congenital fetal abnormalities, such as CMV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…63 A study carried out using a bioinformatic approach showed that infection of human NPCs results in substantial changes in gene up-and down-regulation. 64 In this context, prominent features are represented by the hyper-expression of genes involved in the regulation of nucleic acid metabolism (hallmark of virus replication) and the down-regulation of genes involved in chromosome segregation and DNA replication and repair. 64 In addition, ZIKV infection of the above-mentioned cells results in the activation of several innate immunity pathways, that are different from those observed in other infections known to cause congenital fetal abnormalities, such as CMV.…”
mentioning
confidence: 99%
“…64 In this context, prominent features are represented by the hyper-expression of genes involved in the regulation of nucleic acid metabolism (hallmark of virus replication) and the down-regulation of genes involved in chromosome segregation and DNA replication and repair. 64 In addition, ZIKV infection of the above-mentioned cells results in the activation of several innate immunity pathways, that are different from those observed in other infections known to cause congenital fetal abnormalities, such as CMV. 64 Experiments carried out in more complex systems, such as human cerebral organoids, are consistent with the above reported observations.…”
mentioning
confidence: 99%
“…Thus, ZIKV-infected cells exhibit the characteristic ultrastructural alterations of flavivirusinfected cells (Dick, 1952;Offerdahl et al, 2017). In addition, ZIKV infection provokes changes in the pattern of cellular and viral RNA methylation and induces a major impact on the transcriptome of the host cell (Rolfe et al, 2016).…”
Section: Mechanisms Of Zikv Entry In Human Cells and The Antiviral Rementioning
confidence: 99%
“…Bunun nedeni, Zika virüs enfeksiyonun Dengue ateşi ve Chikungunya enfeksiyonlarına benzer bir tablo oluşturması olabilir (26)(27)(28)35,36) . (10,46) . (47,48) .…”
Section: -1983 Yılları Arasında Zika Virüs Ekvatoryalunclassified
“…Virüsün enfektivitesi E proteininin N terminal glikolizasyonu ile arttırılabilmektedir. Mevcut çalışmalar N-linked glikolizasyondaki değişimlerin, Zika virüsünün transmisyonunda ve komplikasyon gelişimine neden olmasında belirgin bir rol oynayabileceği yönündedir (10)(11)(12)(13) . Zika virüsünün gebelikte geçirilen enfeksiyon ile ilişkili olarak bebekte mikrosefali oluşturmasında temel patolojik mekanizmanın sentrozomlardaki hasar olabileceği öne sürülmektedir (14) .…”
Section: Introductionunclassified